A COMPUTATIONAL STUDY OF FUEL IMPINGEMENT IN THE INTAKE OF A SPARK IGNITION ENGINE - Guldan, Jason Ronald (My University, 2009)
A computational study of fuel impingement in a port fuel injection gasoline engine was performed to gain an understanding of the fuel impingement process, and provide insight into high load fuel delivery, where oil dilution by fuel can be a significant problem. The relatively low intake manifold temperatures and large amount of fuel injected make fuel impingement and oil dilution of particular interest in marine outboard engines. This project included the development of a rezoning subroutine, a single-component fuel study and multi-component fuel study using KIVA. Single-component studies of C6H14, C8H18, C14H30 and C8H17 (gasoline) gave an initial indication of the amount and location of fuel impingement. These results indicated a fuel-composition dependence of the fuel impingement process. ASTM D-86 fuel distillation curves were used to create gasoline multicomponent fuel distributions. The results of the multi-component study showed that the mass-averaged mean molecular weight fuel increased during time, suggesting that the heavy components in the fuel would have significant impact on the fuel film. Additional single-component simulations were conducted with a fuel mass representative of the multi-component distribution to examine what effect heavier (C9H20 and C10H22) test fuels would have on the impingement process. The C9H20 and C10H22 simulations showed a higher fraction of the fuel forming a fuel film, 86.9% and 94.4% of total injected fuel, respectively, compared to 38.6% for C8H18 and 33.2% for C8H17. For the tested conditions, there is a clear transition in the impingement process between C8H18 and lighter hydrocarbons and hydrocarbons that are heavier than C8H18.